Contributions to Research on Native Mexican Plants of Economic Importance in Northeast Mexico - Maiti, Ratikanta (International Journal of Economic Plants, 2015)
The author states a salient out lines of research advances on various aspects of native plants in Northeast of Mexico and high land of Puebla. The native plants studied are Cactus, Mexican plant fibres, medicinal plants, wild fruit tree, wild edible plants such as chile piquin, wild species of Brassica, and Phaseolus, wild maize, and timber yielding plants. The investigation gives the comprehensive idea not only on the composition of the plants, but also information on the individual characteristics distinctly different.